Analisa efektifitas bank sampah sebagai alternatif pengelolaan sampah dalam mencapai smart city di kabupaten kulon progo - Mike Dewanti; Eko Priyo Purnomo; Lubna Salsabila (Universitas Merdeka Malang, 2020)
Abstract This research will focus on analyzing the effectiveness of the waste bank as an alternative to waste management in achieving the concept of smart city in Kulon Progo Regency. The research was conducted to describe how the existence of a garbage bank in Kulon Progo Regency and to analyze how the effectiveness of the waste bank in managing waste in achieving the concept of smart city. This research uses a qualitative method with a descriptive analysis approach. The researcher uses descriptive analysis method, which is an analysis that is intended to explain data from one variable under study. From the research results obtained information that the existence of a garbage bank is experiencing good development because up to 2019 there have been 116 garbage banks. While the effectiveness of the garbage bank has so far been seen to be less effective because it has only been able to manage 10% of the waste generated. Indeed, waste banks make sprouts of economic value and provide benefits to waste producers but have not overcome the problem of waste. So that the concept of smart city on environmental indicators is still not well achieved by the existence of a garbage bank. DOI: 10.26905/pjiap.v5i1.3828